Revenge of the Aztecs - Pfeffer, Susan Beth, 1948- (Jamestown's American portraits, 2000)
In 1923, fourteen-year-old Alicia Martinez is cast in an important silent movie role by her best friend's father, but near-disasters on the Hollywood set seem to be directed at her, and almost anyone could be responsible.